2021
DOI: 10.1108/cms-01-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: independent directors and corporate social responsibility in China

Abstract: Purpose This study aims to examine the effect of independent directors on the corporate social responsibility (CSR) gap – a misalignment between internal and external CSR. More specifically, the authors investigate how two types of independent directors (i.e. politically connected and foreign) affect a firm’s CSR gap in China. Design/methodology/approach The authors use the fixed-effects regression model to analyze the panel dataset, which is conducted by a sample of Chinese publicly listed firms from 2008 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 81 publications
(213 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, to alleviate the endogenous problems brought by the estimation model, OLS regression model with firm- and year-fixed effects estimation was used to test the relationships between green M&A premium and firm value and the moderating role of CSR strategy. The model can effectively control all factors that vary across firms but not over time and all factors that vary over time but not with the firm, which is able to significantly alleviate potential endogeneity problems (Jin et al , 2022). Columns (1)–(3) of Table 7 show the regression results after changing the model.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, to alleviate the endogenous problems brought by the estimation model, OLS regression model with firm- and year-fixed effects estimation was used to test the relationships between green M&A premium and firm value and the moderating role of CSR strategy. The model can effectively control all factors that vary across firms but not over time and all factors that vary over time but not with the firm, which is able to significantly alleviate potential endogeneity problems (Jin et al , 2022). Columns (1)–(3) of Table 7 show the regression results after changing the model.…”
Section: Resultsmentioning
confidence: 99%
“…Although research focusing on aggregate ESG performance and its three pillars is increasing, studies of variations across individual dimensions of ESG pillars are rare (Ongsakul et al , 2020; Jin et al , 2021; Uyar et al , 2022). Variations among ESG dimensions can cause inequality when addressing different types of stakeholders, and as such, this misalignment must be assessed to avoid backlash by neglected stakeholders (Jin et al , 2021). ESG inequality arises from variations across dimensions of its three pillars – i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies concentrated on gaps/inequality/inconsistency among different dimensions of CSR. Among them, Jin et al (2021) examined whether independent directors reduce the gap between internal and external stakeholders, while Ongsakul et al (2020) found that stronger board RAF 22,3 monitoring reduces ESG inequality. Concerning the consequences of CSR inequality, Uyar et al (2022) demonstrated that ESG inequality is detrimental to social reputation, and Al-Shammari et al (2022) found that CSR inequality adversely impacts the otherwise positive connection between CSR and firm performance.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al . (2021a, b) found that more independent female directors played a positive role in promoting the corporate social responsibility practices of Chinese listed companies. Post et al .…”
Section: Introductionmentioning
confidence: 99%
“…(2015) explored the relationship between female directors in UK companies' tendency to disclose GHG and found that female directors significantly increased the GHG disclosure level of UK companies compared to male directors. Moreover, similar findings regarding the relationship between female directors and corporate environmental and sustainable performance can be found in both advanced and emerging economies (Giannetti et al ., 2015; He and Jiang, 2019; Jin, Jiang and Shen, 2021; McGuinness et al ., 2017). For these reasons, we hypothesize that female directors with foreign experience may act as a conduit for corporate green commitment in emerging markets such as China.…”
Section: Introductionmentioning
confidence: 99%